The crystal structure of 4-((6-fluoropyridin-2-yloxy)methyl)benzonitrile, C13H9FN2O - Lu Zhi-Qiang (Zeitschrift für Kristallographie - New Crystal Structures)
C13H9FN2O, triclinic, P1‾$\overline{1}$ (no. 2), a = 7.4664(8) Å, b = 8.2700(7) Å, c = 10.0709(11) Å, α = 76.991(8)°, β = 88.403(9)°, γ = 63.619(10)° V = 540.93(10) Å3, Z = 2, Rgt(F) = 0.0534, wRref(F2) = 0.1644, T = 293(2) K.